Quantitative chest computed tomography combined with plasma cytokines predict outcomes in COVID-19 patients. Issue 8 (August 2022) - Carbonell, Guillermo; Del Valle, Diane Marie; Gonzalez-Kozlova, Edgar; Marinelli, Brett; Klein, Emma; El Homsi, Maria; Stocker, Daniel; Chung, Michael; Bernheim, Adam; Simons, Nicole W.; Xiang, Jiani; Nirenberg, Sharon; et al.
Abstract: Despite extraordinary international efforts to dampen the spread and understand the mechanisms behind SARS-CoV-2 infections, accessible predictive biomarkers directly applicable in the clinic are yet to be discovered. Recent studies have revealed that diverse types of assays bear limited predictive power for COVID-19 outcomes. Here, we harness the predictive power of chest computed tomography (CT) in combination with plasma cytokines using a machine learning and k-fold cross-validation approach for predicting death during hospitalization and maximum severity degree in COVID-19 patients. Patients (n = 152) from the Mount Sinai Health System in New York with plasma cytokine assessment and a chest CT within five days from admission were included. Demographics, clinical, and laboratory variables, including plasma cytokines (IL-6, IL-8, and TNF-α), were collected from the electronic medical record. We found that CT quantitative alone was better at predicting severity (AUC 0.81) than death (AUC 0.70), while cytokine measurements alone better-predicted death (AUC 0.70) compared to severity (AUC 0.66). When combined, chest CT and plasma cytokines were good predictors of death (AUC 0.78) and maximum severity (AUC 0.82). Finally, we provide a simple scoring system (nomogram) using plasma IL-6, IL-8, TNF-α, ground-glass opacities (GGO) to aerated lung ratio and age as new metrics that may be used to monitor patients upon hospitalization and help physicians make critical decisions and considerations for patients at high risk of death for COVID-19. Abstract : Radiology; Chest CT; Cytokines; COVID-19; SARS-CoV-2.